Institutional transformations of the capitals market in a mediterranean Agricultural Land: Almería (1769-1853) - Díaz López, Julián Pablo (Chronica Nova. Revista de Historia Moderna de la Universidad de Granada)
The analysis of the information given by contracts of money loan of the Mortgager Office, allows taking valid conclusions about the behaviour of the capitals market in a mediterranean agricultural land during the last decades of the Old Regime (1769- 1853). The chosen samples are the city of Almería and the town of Cuevas de Almanzora. Evolution of the both cities is clearly different in the chronology of the introduction of the obligations; in the elimination of the Church as the organization which loans the capital; in the presence of a commercial dominant class implicated in this market, earlier in Almería. In both cases exist a debtors and creditors cobweb which links the same people in both groups, and keep similar repayment periods.